Validation of a pharmacological imaging challenge using 11C-buprenorphine and 18F-2-fluoro-2-deoxy-D-glucose positron emission tomography to study the effects of buprenorphine to the rat brain - Soyer, Amélie; Leterrier, Sarah; Breuil, Louise; Goislard, Maud; Leroy, Claire; Saba, Wadad; Thibault, Karine; Bo, Gregory Dal; Bottlaender, Michel; Caillé, Fabien; Goutal, Sébastien; Tournier, Nicolas (Frontiers in Neuroscience, 2023)
Aim Buprenorphine mainly acts as an agonist of mu-opioid receptors (mu-OR). High dose buprenorphine does not cause respiratory depression and can be safely administered to elicit typical opioid effects and explore pharmacodynamics. Acute buprenorphine, associated with functional and quantitative neuroimaging, may therefore provide a fully translational pharmacological challenge to explore the variability of response to opioids in vivo. We hypothesized that the CNS effects of acute buprenorphine could be monitored through changes in regional brain glucose metabolism, assessed using 18F-FDG microPET in rats. Materials and methods First, level of receptor occupancy associated with a single dose of buprenorphine (0.1 mg/kg, s.c) was investigated through blocking experiments using 11C-buprenorphine PET imaging. Behavioral study using the elevated plus-maze test (EPM) was performed to assess the impact of the selected dose on anxiety and also locomotor activity. Then, brain PET imaging using 18F-FDG was performed 30 min after injection of unlabeled buprenorphine (0.1 mg/kg, s.c) vs. saline. Two different 18F-FDG PET acquisition paradigms were compared: (i) 18F-FDG injected i.v. under anesthesia and (ii) 18F-FDG injected i.p. in awake animals to limit the impact of anesthesia. Results The selected dose of buprenorphine fully blocked the binding of 11C-buprenorphine in brain regions, suggesting complete receptor occupancy. This dose had no significant impact on behavioral tests used, regardless of the anesthetized/awake handling paradigm. In anesthetized rats, injection of unlabeled buprenorphine decreased the brain uptake of 18F-FDG in most brain regions except in the cerebellum which could be used as a normalization region. Buprenorphine treatment significantly decreased the normalized brain uptake of 18F-FDG in the thalamus, striatum and midbrain (p < 0.05), where binding of 11C-buprenorphine was the highest. The awake paradigm did not improve sensitivity and impact of buprenorphine on brain glucose metabolism could not be reliably estimated. Conclusion Buprenorphine (0.1 mg/kg, s.c) combined with 18F-FDG brain PET in isoflurane anesthetized rats provides a simple pharmacological imaging challenge to investigate the CNS effects of full receptor occupancy by this partial mu-OR agonist. Sensitivity of the method was not improved in awake animals. This strategy may be useful to investigate de desensitization of mu-OR associated with opioid tolerance in vivo.